Bacterial cellulose as an example product for sustainable production and consumption. Issue 5 (11th July 2017) - Jang, Woo Dae; Hwang, Ji Hyeon; Kim, Hyun Uk; Ryu, Jae Yong; Lee, Sang Yup
Abstract : Life cycle of bacterial cellulose. Sustainable production and consumption of bio‐based products are showcased using bacterial cellulose as an example.